Avelumab + axitinib treatment in older patients with advanced renal cell carcinoma in Japan: Subgroup analyses of post‐marketing surveillance data by age - Mototsugu Oya; Taito Ito; Masashi Sato; Makiko Morita; Masahiro Kajita; Norio Nonomura (Cancer Medicine)
Abstract Introduction Avelumab + axitinib was approved in Japan in December 2019 for the treatment of curatively unresectable or metastatic renal cell carcinoma (RCC) based on results from the JAVELIN Renal 101 trial. Materials and Methods To evaluate the safety and effectiveness of avelumab + axitinib in older patients in general clinical practice in Japan, an ad hoc analysis of data from post‐marketing surveillance (PMS) by age group was conducted. Results The analysis population included 328 patients who had received ≥1 dose of avelumab and were enrolled between December 2019 and May 2021. In total, 100 patients (30.5%) were aged ≤64 years, 130 (39.6%) were aged 65–74 years, and 98 (29.9%) were aged ≥75 years. Within these age groups, adverse drug reactions (ADRs) of safety specifications of any grade occurred in 46 (46.0%), 71 (54.6%), and 56 (57.1%), and of grade ≥3 in 13 (13.0%), 23 (17.7%), and 20 (20.4%), respectively. The most common ADRs of safety specifications across all age groups were thyroid dysfunction, infusion reactions, and hepatic function disorders. Median overall survival (OS) was not reached in any age group; 12‐month OS rates in patients aged ≤64, 65–74, or ≥75 years were 83.8%, 86.2%, and 80.0%, and objective response rates were 31.0%, 43.8%, and 30.6%, respectively. Discussion Analyses of PMS data show the safety and effectiveness of avelumab + axitinib across all age groups of patients with RCC in general clinical practice in Japan. The favorable benefit–risk profile was generally consistent with that observed in previous clinical trials.